PELATIHAN PENGGUNAAN APLIKASI GOOGLE FOR EDUCATION PADA GURU-GURU SMKN 10 MERANGIN - Deni Satria; Rozana Zuhri (Politeknik Negeri Sriwijaya, 2023)
At the beginning of the 2022/2023 Academic Year, SMKN10 Merangin utilized the Maya Class learning facilities and infrastructure that used the Google for Education application. Even though the Google for Education application has been created for an account by each teacher at SMKN 10 Merangin, its use is still not optimal. The Google for Education application is Google's service for the world of education starting at the kindergarten, elementary, junior high, high school and tertiary levels. Google provides solutions for integrated communication by e-mail, calendar, and chat/discussion and collaborative solutions in learning activities. The Google for Education application is a series of applications with real-time synergy and collaboration between students, teachers and school staff that can be accessed using PC computers, notebooks, tablets and even smartphones. This includes email applications, calendars, sites, drives, groups, videos, social media that can be integrated with learning management systems at schools with Google acting as a vendor. The training program supported by the Merangin University research and service institute (LP3M) is running according as expected and successful by predetermined achievement indicators